2022
DOI: 10.1111/pech.12524
|View full text |Cite
|
Sign up to set email alerts
|

Toward a culture of peacebuilding and complex identity in the post‐COVID world

Abstract: This article addresses the questions of what is new about complex identity and what it means for peacebuilding.I begin with the notion that scales and identity must be considered in their totality, as part of a complex bundle of technological, economic, and socio-cultural forces. I also

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…From this, it can be concluded that to matter is to feel valued, and inherently inclusive of the opinions and actions of others. Vorkunova (2022) suggests that having a stable identity is a basic human need, and that stability of identity is enveloped in membership and community, belonging and judgments of worth. Membership and community, which in the case of this research effort, can be considered inclusive of the workplace.…”
Section: Operationalizing Self-worth Judgmentsmentioning
confidence: 99%
“…From this, it can be concluded that to matter is to feel valued, and inherently inclusive of the opinions and actions of others. Vorkunova (2022) suggests that having a stable identity is a basic human need, and that stability of identity is enveloped in membership and community, belonging and judgments of worth. Membership and community, which in the case of this research effort, can be considered inclusive of the workplace.…”
Section: Operationalizing Self-worth Judgmentsmentioning
confidence: 99%